Airworthiness : an introduction to aircraft certification : a guide to understanding JAA, EASA, and FAA standards - De Florio, Filippo (Butterworth-Heinemann, 2006)
Makes a real contribution to understanding flight safety.
Keywords: Airworthiness certificates.; Airplanes -- Airworthiness.; Helicopters -- Airworthiness.; elektronické knihy; electronic books